AL-MAJAZ DALAM Al-QUR’AN: PENGERTIAN, MACAM DAN CONTOHNYA - Dea Novitri; Siti Hartina; Muhammad Fikri Aimar (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
Al-majāz is an important field of study in the science of balaghah that examines the use of words or expressions whose meanings are not taken literally, but rather figuratively, due to a specific relationship and the presence of contextual clues that override the literal meaning. Understanding this field is important because many verses of the Qur’an employ the stylistic device of majāz to enhance the beauty of the language and deepen the conveyed meaning. The results of the study indicate that al-majāz is divided into several types, including majāz lughawi and majāz ‘aqli. Majāz lughawi is further subdivided into majāz mursal and isti‘ārah. In the Qur’an, the use of majāz serves to reinforce the message, create a sense of linguistic beauty, and facilitate human understanding of profound meanings. Examples of majāz in the Qur’an demonstrate the miraculous nature of the Qur’anic language, which is not only beautiful in literary terms but also rich in meaning and life values. Thus, an understanding of al-majāz can help readers comprehend the content of Qur’anic verses more broadly and deeply.